PENGGUNAAN FLY ASH DAN BOTTOM ASH SEBAGAI BAHAN SUBTITUSI MATERIAL CAMPURAN BETON ASPAL LAPIS AUS (AC-WC) - Huldayani, Andi; Syarif, Iif Ahmad (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2023)
ABSTRACT: Burning coal produces waste in the form of fly ash and bottom ash (FABA) which can pollute the environment. This research uses FABA as a material in the wear coated asphalt concrete mixture (AC-WC) which is one way to reduce waste from burning coal with the aim of this research to determine the optimum asphalt content, marshall and volumetric characteristics, and the optimum percentage of FABA use with FABA filler variations 25%, 50%, 75% and 100%. In this research, mixture planning was carried out in two stages of manufacture with the first stage of making test objects to determine KAO without the use of FABA. The second stage is making test objects using KAO by replacing the filler using FABA according to variations. Marshall and volumetric test results showed that KAO in the Laston AC-WC mixture was 6.5%. Based on the marshall and volumetric characteristics of the use of FABA filler, the optimum density value is found at 25% FABA variation with a value range of 2,040-2,062 gr/cm3 and an average of 2,052 gr/cm3. VMA is found in the 50% FABA variation with a value range of 17.888-19.308% and an average of 18.556%. VFB is found in the 75% FABA variation with a value range of 72.224-75.262% and an average of 74.147%. VIM is found in the 50% FABA variation with a value range of 4.663-6.382% and an average of 5.509%. Stability is found in the 100% FABA variation with a value range of 1763.916-2180.989 kg and an average of 1990.767 kg. Flow is found in the 75% FABA variation with a value range of 3.6-5.4 mm and an average of 4.3 mm. MQ is found in the 100% FABA variation with a value range of 335,281-557,520 kg/mm and an average of 498,246 kg/mm. The optimum value of using FABA filler in the wear layer laston mixture (AC-WC) in terms of stability is within 100% variation.Keywords: AC-WC, Filler, FABA, KAO, MarshallABSTRAK: Pembakaran batu bara menghasilkan limbah berupa fly ash dan bottom ash (FABA) yang dapat mencemari lingkungan. Penelitian ini menggunakan FABA sebagai bahan material pada campuran beton aspal lapis aus (AC-WC) merupakan salah satu cara untuk mengurangi limbah hasil pembakaran batu bara dengan tujuan penelitian ini untuk mengetahui kadar aspal optimum, karakteristik marshall dan volumetrik, dan persentase optimum penggunaan FABA dengan variasi filler FABA 25%, 50%, 75% dan 100%. Dalam penelitian ini perencanaan campuran dilakukan dua tahap pembuatan dengan pembuatan benda uji tahap pertama menentukan KAO tanpa penggunaan FABA. Tahap kedua pembuatan benda uji menggunakan KAO dengan mengganti filler menggunakan FABA sesuai variasi. Hasil pengujian marshall dan volumetrik didapatkan KAO pada campuran laston AC-WC yaitu 6,5%. Berdasarkan karakteristik marshall dan volumetrik penggunaan filler FABA memperoleh nilai optimum density terdapat pada variasi FABA 25% dengan rentang nilai 2,040–2,062 gr/cm3 dan rata-rata 2,052 gr/cm3. VMA terdapat pada variasi FABA 50% dengan rentang nilai 17,888–19,308% dan rata-rata 18,556%. VFB terdapat pada variasi FABA 75% dengan rentang nilai 72,224–75,262% dan rata-rata 74,147%. VIM terdapat pada variasi FABA 50% dengan rentang nilai 4,663–6,382% dan rata-rata 5,509%. Stabilitas terdapat pada variasi FABA 100% dengan rentang nilai 1763,916-2180,989 kg dan rata-rata 1990,767 kg. Flow terdapat pada variasi FABA 75% dengan rentang nilai 3,6–5,4 mm dan rata-rata 4,3 mm. MQ terdapat pada variasi FABA 100% dengan rentang nilai 335,281–557,520 kg/mm dan rata-rata 498,246 kg/mm. Nilai optimum penggunaan filler FABA pada campuran lastón lapis aus (AC-WC) ditinjau dari stabilitas terdapat pada variasi 100%.Kata kunci: AC-WC, Filler, FABA, KAO, Marshall